Purely electrical single-molecule memory based on spin torque effect and its preparation method

By utilizing spin moment effect and pure electrical methods in single-molecular memory, combined with heavy metal multi-layer stacked wedge-shaped gate and graphene nanogap array electrode, the problems of high power consumption and limited storage density of traditional storage devices are solved, and high-density and high-speed storage effects are achieved.

CN119562528BActive Publication Date: 2025-04-15NANKAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510124894.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-15
Estimated Expiration
2045-01-27

AI Technical Summary

Technical Problem

Traditional storage devices face problems such as high power consumption, poor data security and limited storage density. Especially in the context of the development of big data and artificial intelligence technologies, how to achieve high-density and high-speed storage has become urgently needed.

Method used

Using pure electrical single-molecule memory based on spin moment effect, the writing and reading of spin information is realized through components such as heavy metal multi-layer stacked wedge-shaped gate, graphene nanogap array electrode, organic radical compounds and magnetic tunnel junctions.

Benefits of technology

It realizes high information read and write speed (ns level) and low operating power consumption (nA level), while having good stability and integration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562528B_ABST
    Figure CN119562528B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of molecular optoelectronic devices, and provides a pure electrical single-molecule memory based on spin torque effect and a preparation method thereof, wherein the memory comprises a multi-layer stacked wedge-shaped gate of a heavy metal, a graphene nanogap array electrode, an organic free radical compound, a magnetic tunnel junction and a non-magnetic metal electrode; the organic free radical compound has a chiral induced spin selection effect, and is connected to the graphene nanogap array electrode through an amide covalent bond to form an organic free radical molecule heterojunction; the graphene nanogap array electrode and the organic free radical compound are assembled on the top of the multi-layer stacked wedge-shaped gate of the heavy metal, and a magnetic tunnel junction and a non-magnetic metal electrode are respectively arranged on both sides of the organic free radical molecule heterojunction. The memory of the present invention can realize the writing and reading of spin information in a purely electrical manner by only controlling the positive and negative voltage, and has a high information reading and writing speed and low operating power consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of molecular optoelectronic devices, and in particular to a pure electrical single-molecule memory based on spin torque effect and a preparation method thereof. Background Art

[0002] Traditional storage devices, such as hard disks and flash memory, have made significant progress in capacity and read / write speed, but they still face problems such as high power consumption, poor data security, and limited storage density. Especially in the context of the rapid development of big data and artificial intelligence technology, how to achieve high-density and high-speed storage while maintaining low power consumption has become a difficult problem that scientists and engineers need to solve urgently. Therefore, researching new storage media and improving storage efficiency has become one of the hot topics in the current information technology field.

[0003] As a promising storage technology, single-molecule memory has attracted more and more attention in recent years. Compared with traditional storage media, single-molecule memory has the advantages of higher storage density, lower power consumption and smaller size. However, the development of single-molecule memory still faces many technical challenges, including how to effectively utilize the spin torque effect in single molecules to achieve efficient data storage and reading. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention provides a pure electrical single-molecule memory based on the spin torque effect and a preparation method thereof, so as to obtain a pure electrical single-molecule memory based on the spin torque effect with high information reading and writing speed, low operating power consumption, good stability and integration, so as to realize the writing and reading of spin information in a purely electrical manner by only controlling the positive and negative voltage, and have high information reading and writing speed and low operating power consumption.

[0005] The present invention provides a pure electrical single-molecule memory based on spin torque effect, comprising:

[0006] Multilayer stacked wedge gates of heavy metals, graphene nanogap array electrodes, organic radical compounds, magnetic tunnel junctions, and nonmagnetic metal electrodes;

[0007] The organic free radical compound has a chirality-induced spin-selective effect and can self-assemble into two α-helical structures with opposite chirality. The organic free radical compound is connected to the graphene nanogap array electrode through an amide covalent bond to form an organic free radical molecular heterojunction;

[0008] A magnetic tunnel junction and a non-magnetic metal electrode are respectively arranged on both sides of the organic free radical molecule heterojunction, and the graphene nanogap array electrode, the organic free radical compound, the magnetic tunnel junction and the non-magnetic metal electrode are all assembled on the top of the multi-layer stacked wedge-shaped gate of the heavy metal.

[0009] Furthermore, the structural formula of the organic free radical compound is:

[0010]

[0011] Wherein, n is an integer of 6 to 10; m is an integer of 6 to 10; R is

[0012] or or or .

[0013] Furthermore, the magnetic tunnel junction includes a tunneling layer and a magnetic electrode stacked in sequence, the tunneling layer is connected to the multi-layer stacked wedge-shaped gate of the heavy metal, the tunneling layer includes any one of aluminum oxide, magnesium oxide or molybdenum disulfide, the magnetic electrode includes any one of iron, cobalt or nickel, and the non-magnetic metal electrode includes an adhesive layer and an Au electrode stacked in sequence, and the adhesive layer is connected to the multi-layer stacked wedge-shaped gate of the heavy metal.

[0014] Furthermore, the heavy metal multilayer stacked wedge-shaped gate includes a tantalum layer, a cobalt iron boron layer and a tantalum oxide layer stacked in sequence, wherein the bottom is the tantalum layer and the top is the tantalum oxide layer, and the tantalum oxide layer forms a continuously changing thickness gradient along the length direction.

[0015] Furthermore, the graphene nanogap array electrode is adapted to the size of the organic free radical compound.

[0016] Furthermore, it also includes a hexagonal boron nitride protective layer, which covers the magnetic tunnel junction, the non-magnetic metal electrode and the top of the organic free radical molecular heterojunction.

[0017] The present invention also provides a method for preparing a pure electrical single-molecule memory based on the spin torque effect, and preparing the above-mentioned pure electrical single-molecule memory based on the spin torque effect.

[0018] The steps include:

[0019] S1: Preparation of organic free radical compounds;

[0020] S2: Preparation of heavy metal multilayer stacked wedge-shaped gates;

[0021] S3: preparing a graphene nanogap array electrode, and preparing an asymmetric magnetic tunnel junction and a non-magnetic metal electrode on both sides of the graphene nanogap array electrode;

[0022] S4: Connecting organic free radical compounds to graphene nanogap array electrodes through covalent bonds to obtain single-molecule spin memory;

[0023] S5: Assemble a single-molecule spin memory directly above a multi-layer stacked wedge-shaped gate of a heavy metal and prepare a hexagonal boron nitride protective layer directly above the single-molecule spin memory to obtain a purely electrical single-molecule memory based on the spin torque effect.

[0024] Further, S2 includes the following steps:

[0025] S21: Depositing SiO2 on the thermally oxidized silicon wafer;

[0026] S22: using DC magnetron sputtering technology to deposit a tantalum layer on SiO2 at room temperature, and a cobalt iron boron layer on the tantalum layer;

[0027] S23: depositing a tantalum oxide layer on the cobalt iron boron layer, wherein the top tantalum oxide layer grows in a wedge shape to form a continuously changing thickness gradient along the length direction; exposing the layer to radio frequency oxygen / argon plasma to form a tantalum oxide layer, and obtaining a gate sample;

[0028] S24: annealing the gate sample to obtain a multi-layer stacked wedge-shaped gate of heavy metal.

[0029] Furthermore, S3 includes the following steps:

[0030] S31: growing a single layer of graphene on the surface of copper foil by chemical vapor deposition and transferring it to the surface of silicon wafer by means of polymethyl methacrylate;

[0031] S32: using a UV lithography machine to perform a first photolithography, making a marking pattern on the graphene surface and evaporating metal chromium and gold to obtain graphene with a mark;

[0032] Using an ultraviolet lithography machine to perform a second photolithography, making a stripe pattern on the surface of the labeled graphene, and etching it in a reactive ion etcher to obtain graphene strips;

[0033] The third photolithography was performed using an ultraviolet lithography machine to make an electrode pattern on the left side of the graphene strip, and magnesium oxide and cobalt were sequentially evaporated by magnetron sputtering to obtain an asymmetric magnetic tunnel junction on the left side of the graphene strip.

[0034] The fourth photolithography was performed using an ultraviolet lithography machine to make an electrode pattern on the right side of the graphene strip, and chromium and gold were sequentially evaporated by magnetron sputtering to obtain a non-magnetic metal electrode on the right side of the graphene strip;

[0035] S33: Spin-coat a polymethyl methacrylate protective layer on the surface of the graphene strip, use electron beam exposure technology to make a polymethyl methacrylate dotted window, use a reactive ion etcher to penetrate the polymethyl methacrylate dotted window to break the graphene into a head-to-head triangular array, and obtain a graphene nanogap array electrode by electrical burning.

[0036] Further, S4 includes the following steps:

[0037] S41: mixing an organic free radical compound and a dehydration activator, and dissolving the mixture in a solvent in an anhydrous and oxygen-free environment to obtain a mixed solution;

[0038] S42: sealing the device containing the graphene nanogap point electrode in a two-necked flask, repeatedly performing aeration and ventilation operations, adding the mixed solution, making the reaction in an inert gas atmosphere, reacting for 24 to 48 hours under dark conditions, taking out, washing, and drying to obtain a single-molecule spin memory;

[0039] The dehydration activator is selected from any one of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloric acid, dicyclohexylcarbodiimide or N,N'-diisopropylcarbodiimide; the solvent is selected from any one of pyridine, dimethyl sulfoxide or trichlorobenzene; the inert gas is argon or nitrogen; the molar ratio of the organic free radical compound to the dehydration activator is 1:(20-40); the concentration of the dehydration activator is 2×10 -3 ~ 4×10 -3 mol / L.

[0040] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:

[0041] The organic free radical compound has a chirality-induced spin selection effect and a singlet / triplet fast switching capability at room temperature. When currents in different directions pass through alpha helices of different chirality, spin polarizations in different directions are generated due to the CISS effect. The spin polarized current is injected into the free radical molecule, causing the spin flip of the free radical molecule under the action of the spin transfer torque effect, generating high and low conductivity states, representing binary data "0" and "1" respectively, for storing information; the organic free radical compound can be stably connected to the graphene nanogap array through amide covalent bonds to form an organic free radical molecule heterojunction; the magnetic tunnel junction and the non-magnetic metal electrode generate tunneling magnetoresistance and spin transfer torque effects to assist in information reading and writing operations; the multi-layer stacked wedge-shaped gate containing heavy metals can achieve deterministic magnetization flipping in the vertical direction when current passes through the equivalent magnetic field. The purely electrical single-molecule memory based on the spin torque effect provided in the present application can realize the writing and reading of spin information in a purely electrical way by simply controlling the positive and negative voltage, and has a high information reading and writing speed (ns) and low operating power consumption (nA).

[0042] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 It is a schematic diagram of the overall three-dimensional structure of the pure electrical single-molecule memory based on the spin torque effect provided by the present invention.

[0045] Figure 2 It is a schematic diagram of a multi-layer stacked wedge-shaped gate of a pure electrical single-molecule memory based on the spin torque effect provided by the present invention.

[0046] Figure 3 The present invention provides a current-bias characteristic curve of the pure electrical single-molecule memory based on the spin torque effect before and after the connection of molecules.

[0047] Figure 4 The present invention is a schematic diagram of information reading and writing of a pure electrical single-molecule memory based on spin torque effect when no gate voltage is applied.

[0048] Figure 5The present invention provides a schematic diagram of information reading and writing of a pure electrical single-molecule memory based on spin torque effect when gate voltage is applied.

[0049] Figure 6 The invention provides a pure electrical single-molecule memory based on the spin torque effect. R -Peptide synthesis roadmap.

[0050] Figure 7 The invention provides a pure electrical single-molecule memory based on the spin torque effect. S -Peptide synthesis roadmap.

[0051] Reference numerals:

[0052] 1. Silicon wafer; 2. SiO2 layer; 3. Tantalum layer; 4. Cobalt iron boron layer; 5. Tantalum oxide layer; 6. Tunneling layer; 7. Adhesive layer; 8. Magnetic electrode; 9. Au electrode; 10. Graphene nanogap array electrode; 11. Organic free radical compound; 12. h-BN protective layer. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.

[0054] In the following examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0055] Combine the following Figures 1 to 7 The invention describes a pure electrical single-molecule memory based on spin torque effect and a preparation method thereof.

[0056] like Figure 1 As shown, a pure electrical single-molecule memory based on spin torque effect includes: a multi-layer stacked wedge-shaped gate of heavy metal, a graphene nanogap array electrode 10, an organic free radical compound 11, a magnetic tunnel junction and a non-magnetic metal electrode;

[0057] The organic free radical compound 11 has a chirality-induced spin-selective effect and can self-assemble into two α-helical structures with opposite chirality. The organic free radical compound 11 is connected to the graphene nanogap array electrode 10 through an amide covalent bond to form an organic free radical molecular heterojunction;

[0058] The graphene nanogap array electrode 10 and the organic free radical compound 11 are assembled on top of a multi-layer stacked wedge-shaped gate of a heavy metal, and a magnetic tunnel junction and a non-magnetic metal electrode are respectively arranged on both sides of the organic free radical molecule heterojunction.

[0059] Organic free radical molecular heterojunction with chiral induced spin selection effect (CISS) can quickly switch its high and low conductivity states when the voltage direction is switched, representing binary data "0" and "1" respectively, as a carrier of information.

[0060] It contains left-handed chiral α-helix and right-handed chiral α-helix. When currents in different directions pass through α-helices of different chirality, spin polarizations in different directions are generated due to the effect. The spin-polarized current is injected into the free radical molecules, causing the spin flip of the free radical molecules under the action of the spin transfer torque effect, thereby realizing the writing of information. The switching between "0" and "1" can be achieved by changing the positive and negative voltage.

[0061] The structural formula of the organic free radical compound 11 is:

[0062]

[0063] Wherein, n is an integer of 6 to 10; m is an integer of 6 to 10; R is

[0064] or or or .

[0065] In some specific embodiments of the present invention, the chemical structural formula of the organic free radical compound 11 is any one of A1 to A4, wherein the chemical structural formula of A1 is:

[0066]

[0067] The chemical structure of A2 is:

[0068] The chemical structure of A3 is:

[0069]

[0070] The chemical structure of A4 is:

[0071]

[0072] The magnetic tunnel junction includes a tunneling layer 6 and a magnetic electrode 8, the tunneling layer 6 includes any one of aluminum oxide, magnesium oxide (MgO) or molybdenum disulfide, the magnetic electrode 8 includes any one of iron, cobalt or nickel metals, the non-magnetic metal electrode includes a bonding layer 7 and an Au electrode 9, the bonding layer 7 includes a chromium (Cr) bonding layer.

[0073] The asymmetric magnetic tunnel junction and the non-magnetic metal electrode, together with the organic free radical molecular heterojunction, form the basic structure of the spin transfer torque (STT) effect. The basic principle of STT is that spin-polarized electrons interact with local magnetic moments and transfer their angular momentum to local magnetic moments. The spin transfer torque effect can be used to achieve the reversal of the magnetic moment of the free layer.

[0074] In some specific embodiments of the present invention, the magnetic electrode 8 includes any one of iron, cobalt or nickel, and the spin-up and spin-down electronic states of these materials are unevenly distributed near the Fermi level, thereby generating a net magnetic moment, which serves as a fixed layer; the tunneling layer 6 includes any one of aluminum oxide, magnesium oxide or molybdenum disulfide, which only allows electrons to pass through in a tunneling manner, thereby improving the efficiency of spin-polarized current injection; the magnetic moment of the organic free radical molecular heterojunction is relatively small and can be easily changed by external angular momentum, and serves as a free layer.

[0075] When electrons flow from the fixed layer to the free layer, they are first polarized by the fixed layer to form a spin-polarized current. When electrons pass through the free layer, due to the STT effect, the magnetic moment of the free layer can be flipped to a direction parallel to the fixed layer. At this time, the information is recorded as "0". Conversely, when electrons flow from the free layer to the fixed layer, they are first polarized by the free layer. When the electrons in the spin-polarized current pass through the fixed layer, due to the large coercive force of the fixed layer and the stable direction of the magnetic moment, the electrons with different directions from the magnetic moment of the fixed layer will be reflected back to the free layer, thereby flipping the magnetic moment of the free layer to a direction antiparallel to the fixed layer. At this time, the information is recorded as "1".

[0076] like Figure 2 As shown, the heavy metal multilayer stacked wedge-shaped gate is a tantalum layer 3, a cobalt iron boron layer 4 and a tantalum oxide layer 5 stacked in sequence, wherein the bottom is a tantalum (Ta) layer and the top is a tantalum oxide (TaOx) layer, and the tantalum oxide layer 5 forms a continuously changing thickness gradient along the length direction.

[0077] In some specific embodiments of the present invention, the heavy metal multilayer stacked wedge gate Ta / CoFeB / TaOx has a rectangular top view with a length and width of 2.2 mm×0.02 mm, and is located directly below the organic free radical molecular heterojunction. The deposition thickness of the bottom tantalum (Ta) layer is 5~10 nm, the deposition thickness of the cobalt iron boron layer 4 is 1~2 nm, and the top tantalum oxide (TaOx) layer forms a thickness gradient that continuously changes from 0.81 nm to 2.13 nm along the length direction of the rectangle.

[0078] When current is passed along the heavy metal, in addition to the spin-orbit moment, the newly introduced planar structural asymmetry will induce two additional moments. Under the combined action of these moments, deterministic magnetization reversal can be achieved without the need for an external magnetic field. This writing method eliminates the initial delay and increases the writing speed. And with the assistance of the spin Hall effect, the current flowing through the magnetic tunnel junction can be reduced to a lower level, reducing the probability of barrier breakdown.

[0079] The graphene nanogap array electrode 10 is adapted to the size of the organic free radical compound 11 .

[0080] In some specific embodiments of the present invention, the end of the graphene nanogap array electrode 10 is a carboxyl group, which can form a stable amide bond with the amino group at the end of the organic free radical compound 11 through an amide condensation reaction, which can increase the charge transfer speed, thereby improving the operating speed and stability of the device, and allowing the device to switch sensitively and quickly between high and low conductivity states.

[0081] The graphene nanogap array electrode 10 has a thickness of 0.5-2 nm and a gap distance of 2-20 nm, and is located directly above the multilayer stacked wedge-shaped gate containing heavy metals. The single-molecule organic free radical heterojunction with chiral induced spin selection effect has a thickness of 0.5-2 nm and is located directly above the multilayer stacked wedge-shaped gate containing heavy metals.

[0082] It also includes a hexagonal boron nitride (h-BN) protective layer, and the h-BN protective layer 12 covers the top of the magnetic tunnel junction, the non-magnetic metal electrode and the organic free radical molecular heterojunction.

[0083] In some specific embodiments of the present invention, the h-BN protective layer 12 covers the top of the asymmetric magnetic tunnel junction, the non-magnetic metal electrode and the organic free radical molecular heterojunction. On the one hand, it suppresses the molecular conformational disturbance through van der Waals contact and reduces electrical noise; on the other hand, it isolates the external electromagnetic interference and the air effect, thereby improving the storage stability and anti-interference ability of the device.

[0084] The organic free radical compound has a chirality-induced spin selection effect and a singlet / triplet fast switching capability at room temperature. When currents in different directions pass through alpha helices of different chirality, spin polarizations in different directions are generated due to the CISS effect. The spin polarized current is injected into the free radical molecule, causing the spin flip of the free radical molecule under the action of the spin transfer torque effect, generating high and low conductivity states, representing binary data "0" and "1" respectively, for storing information; the organic free radical compound can be stably connected to the graphene nanogap array through an amide covalent bond to form an organic free radical molecule heterojunction; the magnetic tunnel junction and the non-magnetic metal electrode generate tunneling magnetoresistance and spin transfer torque effects to assist in information reading and writing operations; the multi-layer stacked wedge-shaped gate containing heavy metals can achieve deterministic magnetization flipping in the vertical direction when current passes through the equivalent magnetic field. The pure electrical single-molecule memory based on the spin torque effect provided by the present invention can realize the writing and reading of spin information in a purely electrical way only by controlling the positive and negative voltage, and has a high information reading and writing speed, the reading and writing speed is at the ns level, and the operating power consumption is low, the operating power is at the nA level.

[0085] A method for preparing a pure electrical single-molecule memory based on a spin torque effect, comprising the following steps:

[0086] S1: Preparation of organic free radical compounds;

[0087] Synthesis of A1:

[0088]

[0089] 1.0 mmol R -peptide, 1.1 mmol EDCI (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride), 0.1 mmol DMAP (p-dimethylaminopyridine) 5 mL DCM (dichloromethane) solution was stirred at room temperature for 15 min, and then 1.0 mmol triangular ene (TAE-NH2) molecule 1 mL DCM solution was slowly added, the reaction mixture was stirred at room temperature for 12 h, the reaction was quenched with water, and then extracted with DCM, washed with sodium bicarbonate aqueous solution, and the organic phase was combined, dried, and concentrated to obtain right-handed helical triangular ene ( R -TAE), and then purified by column chromatography to obtain R -TAE.

[0090] 1 H NMR (400 MHz, Chloroform- d ) δ 9.40 (s, 1H), 8.07 (d, J= 1.1 Hz,1H), 8.06 (d, J = 1.1 Hz, 1H), 7.86 (dt, J = 8.0, 0.9 Hz, 1H), 7.81 (dt, J = 7.7,0.8 Hz, 1H), 7.60 – 7.56 (m, 2H), 7.52 – 7.46 (m, 5H), 7.37 (t, J = 8.0 Hz,7H), 7.25 – 7.19 (m, 2H), 7.17 – 7.10 (m, 5H), 6.66 – 6.62 (m, 2H), 5.57 (d, J = 7.1 Hz, 1H), 5.19 (d, J = 0.7 Hz, 2H), 4.33 – 4.25 (m, 7H), 4.23 – 4.16 (m,2H), 4.07 (d, J = 5.6 Hz, 1H), 2.15 (s, 6H), 1.72 – 1.52 (m, 22H), 1.41 (s, 9H), 0.93 – 0.78 (m, 48H).

[0091] 13 C NMR (100 MHz, Chloroform- d ) δ 173.33, 140.11, 138.13, 132.94,131.66, 131.18, 129.87, 128.14, 127.35, 127.20, 127.03, 126.82, 122.33,121.21, 116.38, 52.87, 52.37, 52.35, 52.25, 51.56, 51.43, 40.88, 40.48,39.94, 28.33, 26.19, 24.53, 24.43, 24.37, 22.43.

[0092] Will S A solution of peptide (1.0 mmol), EDCI (1.1 mmol), and DMAP (0.1 mmol) in DCM (5 mL) was stirred at room temperature for 15 min, and then slowly added R-TAE molecule (1.0 mmol) in DCM solution (1 mL), the reaction mixture was stirred at room temperature for 12 h, the reaction was quenched with water, extracted with DCM, washed with sodium bicarbonate aqueous solution, the organic phases were combined, dried, and concentrated to obtain a crude product, and then piperidine (3 mL) was added dropwise to the N,N-dimethylformamide (DMF) solution (7 mL) of the above crude product under a nitrogen atmosphere. The mixed system was stirred at room temperature for 12 h, extracted with dichloromethane and sodium bicarbonate solution, the organic phases were combined, dried, and concentrated, and then purified by column chromatography to obtain right-hand helix-triangular ene-left-hand helix ( R -TAE- S ).

[0093] 1 H NMR (400 MHz, Chloroform- d ) δ 9.40 (s, 2H), 8.07 (dd, J = 7.6, 1.2Hz, 2H), 7.81 (dt, J = 7.7, 0.9 Hz, 2H), 7.60 – 7.56 (m, 4H), 7.52 – 7.45 (m,6H), 7.37 (d, J = 8.0 Hz, 11H), 7.24 – 7.12 (m, 9H), 5.19 (d, J = 1.0 Hz, 1H),5.10 (d, J = 0.8 Hz, 1H), 4.37 – 4.16 (m, 14H), 3.63 (dp, J = 20.0, 5.8 Hz, 2H),2.92 (dd, J = 7.9, 5.5 Hz, 2H), 2.66 (dd, J = 8.0, 5.4 Hz, 2H), 1.75 – 1.49 (m,52H), 0.94 (d, J = 6.9 Hz, 6H), 0.91 – 0.86 (m, 48H), 0.86 – 0.81 (m, 42H).

[0094] 13 C NMR (100 MHz, Chloroform- d ) δ8, 173.33, 131.18, 129.87, 127.20,127.03, 126.82, 122.33, 121.21, 52.41, 52.37, 50.90, 43.07, 42.03, 40.48,39.95, 26.19, 24.97, 24.53, 24.37, 22.43, 22.39.

[0095] A2, A3 and A4 were prepared using the same method and steps as A1.

[0096] The synthetic route of TAE-NH2 is as follows:

[0097]

[0098] Under nitrogen atmosphere, 4-aminophenylmagnesium bromide solution (2.5 mmol) was added dropwise to 2-(10-mesitylene anthracene-9-)isophthalaldehyde (1.0 mmol) in tetrahydrofuran (THF) solution (10 mL) at 0 °C. After 2 h of reaction, water was added to quench the reaction, and the DCM solution was used for extraction. The organic phase was combined, dried, and concentrated, and recrystallized to obtain the diol product. Then, under nitrogen atmosphere, boron trifluoride (BF3) in ether solution (10.0 mmol) was added dropwise to the dichloromethane solution (10 mL) of the above diol product, and the reaction was monitored by thin layer chromatography until the end. Extraction was performed with dichloromethane, and the organic phase was combined, dried, and concentrated, and then purified by column chromatography to obtain TAE-NH2.

[0099] 1 H NMR (400 MHz, Chloroform- d ) δ 8.07 (dd, J = 7.7, 1.1 Hz, 2H), 7.81(dt, J = 7.7, 0.9 Hz, 2H), 7.53 – 7.46 (m, 4H), 7.38 – 7.33 (m, 1H), 7.15 –7.11 (m, 4H), 6.86 (s, 2H), 6.66 – 6.62 (m, 4H), 4.17 (d, J = 5.7 Hz, 2H), 4.07(d, J = 5.7 Hz, 2H), 2.25 (s, 3H), 2.21 (s, 6H).

[0100] 13 C NMR (100 MHz, Chloroform-d ) δ 146.30, 146.23, 138.14, 137.49,137.46, 137.24, 136.81, 136.75, 136.33, 135.49, 134.67, 134.47, 133.57,132.36, 131.62, 131.60, 131.02, 131.00, 130.98, 130.96, 129.29, 129.28,128.09, 126.74, 126.69, 126.58, 126.57, 126.48, 126.47, 126.42, 121.98,121.96, 116.27, 116.25, 116.24, 116.23, 57.12, 52.75, 21.61, 21.57, 21.29.

[0101] The structural formula of R-peptide is:

[0102]

[0103] R -Synthesis routes of peptides such as Figure 6 As shown,

[0104] R -The peptides were synthesized using the standard Fmoc protected solid phase synthesis (SPPS) method. The specific steps are as follows:

[0105] First, Wang resin was swollen in N,N-dimethylformamide (DMF) for 15 min to fully expose the reaction site, then 30% piperidine / DMF solution was added and shaken for 15 min to remove the Fmoc protecting group. The resin was blue-purple when detected by ninhydrin, indicating that the deprotection was successful. R-configuration amino acid, HATU (peptide condensation reagent) and N,N-diisopropylethylamine (DIEA) were added in an amount 4 times the molar equivalent of the resin, and 6 times the molar equivalent of the resin were added. After shaking for 1 h, the resin was washed with DMF, CH3OH and CH2Cl2. The resin was light yellow when detected by ninhydrin, indicating that the amino acid condensation was successful. After removing the Fmoc protecting group again with 30% piperidine / DMF solution, amino acid, HATU and DIEA were added to carry out the coupling reaction of the next amino acid, and the operation was repeated until all amino acids were connected. Finally, 95% TFA / 2.5% TIPS / 2.5% H2O (volume ratio) was added as a cutting agent and reacted with the resin for 3 hours to separate the peptide from the resin. The cutting liquid was collected by filtration and concentrated by a rotary evaporator. Then, -20°C ether was added to precipitate, and the precipitate was collected by centrifugation to obtain a crude peptide product. The product was purified by preparative reversed-phase high-performance liquid chromatography (HPLC) (C18, 10 μm, 150Å, 30×150 mm) equipped with a Durashell C18 separation column. The mobile phase gradient was set from "5% acetonitrile + 95% water" (volume ratio) to "95% acetonitrile + 5% water" (volume ratio), with a flow rate of 10 mL / min. The filtrate corresponding to the target absorption peak was collected and lyophilized to obtain the pure R-peptide product.

[0106] 1 H NMR (400 MHz, Chloroform- d ) δ 9.56 (s, 1H), 7.37 (t, J = 8.0 Hz,6H), 5.65 (d, J = 8.4 Hz, 1H), 5.57 (d, J = 7.1 Hz, 1H), 4.44 – 4.11 (m, 8H), 1.79 – 1.46 (m, 24H), 1.41 (s, 9H), 0.95 (d, J = 6.1 Hz, 3H), 0.92 – 0.87 (m, 24H), 0.86 – 0.80 (m, 21H).

[0107] 13 C NMR (100 MHz, Chloroform- d) δ .73, 173.77, 173.23, 173.17,173.11, 173.09, 173.06, 173.00, 155.57, 80.06, 56.38, 52.82, 52.76, 52.71,52.70, 52.63, 52.57, 52.30, 41.18, 40.90, 40.07, 40.03, 39.98, 39.94, 39.91,39.62, 28.33, 25.26, 24.56, 24.53, 24.51, 24.49, 24.47, 24.44, 22.58,22.56, 22.55, 22.53, 22.52, 22.51, 22.50, 22.49, 22.47, 22.46, 22.45, 22.44,22.42, 22.41, 22.40.

[0108] S -The structural formula of the polypeptide is:

[0109]

[0110] S -Peptide synthesis routes such as Figure 7 As shown, S-The synthesis of the peptide was carried out by the standard Fmoc protection solid phase synthesis method (SPPS), and the specific steps are as follows: First, Wang resin was swollen in DMF for 15 min to fully expose the reaction site, and then 30% piperidine / DMF solution was added and shaken for 15 min to remove the Fmoc protecting group. The resin was blue-purple when detected by ninhydrin, indicating that the deprotection was successful. R-configuration amino acid, HATU and DIEA, which were 4 times the molar equivalent of the resin, were added, and after shaking for 1 h, the resin was washed with DMF, CH3OH and CH2Cl2. The resin was light yellow when detected by ninhydrin, indicating that the amino acid condensation was successful. After removing the Fmoc protecting group again with 30% piperidine / DMF solution, amino acid, HATU and DIEA were added to carry out the coupling reaction of the next amino acid, and the operation was repeated until all amino acids were connected. Finally, 95% trifluoroacetic acid (TFA) / 2.5% triisopropylsiloxy (TIPS) / 2.5% H2O (volume ratio) was added as a cutting agent and reacted with the resin for 3 hours to separate the peptide from the resin. The cutting liquid was collected by filtration and concentrated using a rotary evaporator. Then, -20°C ether was added to precipitate. The precipitate was collected by centrifugation to obtain a crude peptide product. Purification was performed using a preparative reverse-phase HPLC (C18, 10μm, 150Å, 30×150mm) equipped with a Durashell C18 separation column. The mobile phase gradient was set from "5% acetonitrile + 95% water" to "95% acetonitrile + 5% water" at a flow rate of 10 mL / min. The filtrate corresponding to the target absorption peak was collected and freeze-dried to obtain S -Pure polypeptide product.

[0111] 1 H NMR (400 MHz, Chloroform- d ) δ 9.56 (s, 1H), 7.37 (t, J = 8.0 Hz,6H), 5.65 (d, J = 8.4 Hz, 1H), 5.57 (d, J = 7.1 Hz, 1H), 4.49 – 4.16 (m, 8H), 1.76 – 1.47 (m, 24H), 1.41 (s, 9H), 0.95 (d, J = 6.1 Hz, 3H), 0.92 – 0.87 (m, 24H), 0.86 – 0.81 (m, 21H).

[0112] 13 C NMR (100 MHz, Chloroform- d ) δ.73, 173.77, 173.23, 173.17,173.11, 173.09, 173.06, 173.00, 155.57, 80.06, 56.38, 52.82, 52.76, 52.71,52.70, 52.63, 52.57, 52.30, 41.18, 40.90, 40.07, 40.03, 39.98, 39.94, 39.91,39.62, 28.33, 25.26, 24.56, 24.53, 24.51, 24.49, 24.47, 24.44, 22.58,22.56, 22.55, 22.53, 22.52, 22.51, 22.50, 22.49, 22.47, 22.46, 22.45, 22.44,22.42, 22.41, 22.40.

[0113] S2: Preparation of heavy metal multilayer stacked wedge-shaped gates;

[0114] S21: Depositing SiO2 on the thermally oxidized silicon wafer 1; the size of the silicon wafer 1 is 10 mm×10 mm, and the thickness of the SiO2 layer 2 is 300 nm;

[0115] S22: using a DC magnetron sputtering technique to deposit a tantalum layer 3 on the SiO2 layer 2 at room temperature, and a cobalt iron boron layer 4 on the tantalum layer 3, the deposition length and width dimensions are 2.2 mm×0.02 mm, the deposition thickness of the Ta layer 3 is 5 nm, and the deposition thickness of the cobalt iron boron layer 4 is 1 nm;

[0116] S23: depositing a tantalum oxide layer 5 on the cobalt iron boron layer 4, wherein the top tantalum oxide layer 5 grows in a wedge shape, and a thickness gradient continuously changing from 0.81 to 2.13 nm is formed along the length direction; exposing to radio frequency oxygen (O2) / argon (Ar) plasma for 100 seconds to form a TaOx layer 5, and obtaining a gate sample;

[0117] S24: annealing the gate sample to obtain a multilayer stacked wedge-shaped gate of heavy metal, wherein the annealing treatment is annealing at 200° C. for 30 minutes to enhance the perpendicular magnetic anisotropy of the Ta / CoFeB / TaOx wedge-shaped gate;

[0118] S3: preparing a graphene nanogap array electrode, and preparing an asymmetric magnetic tunnel junction and a non-magnetic metal electrode on both sides of the graphene nanogap array electrode;

[0119] S31: Growing a single layer of graphene on the surface of copper foil by chemical vapor deposition and transferring it to the surface of silicon wafer with the help of polymethyl methacrylate (PMMA);

[0120] S32: using a UV lithography machine to perform a first photolithography, making a marking pattern on the graphene surface and evaporating metal chromium and gold to obtain graphene with a mark;

[0121] A second photolithography was performed using an ultraviolet lithography machine to make a stripe pattern on the surface of the labeled graphene, and then the stripe was etched in a reactive ion etcher to obtain a graphene strip. The size of the graphene strip was 2.15 mm × 0.03 mm.

[0122] The third photolithography was performed using an ultraviolet lithography machine to make an electrode pattern on the left side of the graphene strip, and magnesium oxide (MgO) and cobalt (Co) were sequentially evaporated by magnetron sputtering to obtain an asymmetric magnetic tunnel junction on the left side of the graphene strip; the width of the electrode pattern was 3μm, the thickness of MgO was 0.8 nm, and the thickness of Co was 80 nm.

[0123] The fourth photolithography was performed using an ultraviolet lithography machine to make an electrode pattern on the right side of the graphene strip, and chromium and gold were sequentially evaporated by magnetron sputtering to obtain a non-magnetic metal electrode on the right side of the graphene strip; the width of the electrode pattern was 3 μm, the thickness of Cr was 10-20 nm, and the thickness of Au was 80-100 nm;

[0124] S33: Spin-coat a PMMA protective layer on the surface of the graphene strip, and use electron beam lithography (EBL) to make PMMA dotted windows, each with a size of 150 nm × 5 nm. Use a reactive ion etcher (RIE) through the PMMA dotted windows to break the graphene into head-to-head triangle arrays, and then electrically burn them to obtain graphene nanogap array electrodes;

[0125] S4: Connecting organic free radical compounds to graphene nanogap array electrodes through covalent bonds to obtain single-molecule spin memory;

[0126] S41: mixing an organic free radical compound and a dehydration activator, and dissolving the mixture in a solvent in an anhydrous and oxygen-free environment to obtain a mixed solution;

[0127] S42: sealing the device containing the graphene nanogap point electrode in a two-necked flask, repeatedly performing aeration and ventilation operations, adding the mixed solution, making the reaction in an inert gas atmosphere, reacting for 24 to 48 hours under dark conditions, taking out, washing, and drying to obtain a single-molecule spin memory;

[0128] The dehydration activator is selected from any one of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloric acid, dicyclohexylcarbodiimide or N,N'-diisopropylcarbodiimide; the solvent is selected from any one of pyridine, dimethyl sulfoxide or trichlorobenzene; the inert gas is argon or nitrogen; the molar ratio of the organic free radical compound to the dehydration activator is 1:(20-40); the concentration of the dehydration activator is 2×10 -3 ~ 4×10 -3 mol / L.

[0129] S5: Assemble a single-molecule spin memory directly above a multilayer stacked wedge-shaped gate of a heavy metal and prepare an h-BN protective layer directly above the single-molecule spin memory to obtain a purely electrical single-molecule memory based on the spin torque effect.

[0130] In some embodiments of the present invention, the 1H and 13CNMR spectra of the compounds were recorded on Variance Mercury plus 300MHz and Bruker ARX500NMR spectrometers; all chemical shifts of 1H were referenced to tetramethylsilane (TMS, δ = 0.00ppm) or deuterated chloroform (Chloroform-d, CDCl3, δ = 7.26ppm), and 13CNMR chemical shifts were referenced to CDCl3 (δ = 77.00ppm). Mass spectra were recorded on a Bruker APEX IV mass spectrometer.

[0131] Electrical tests were performed under vacuum conditions (<1×10 -4 Pa).

[0132] Test instruments: semiconductor parameter analyzer (Keysight, B1500A), probe station (Janis Research Company, ST-500), comprehensive physical property test system (Quantum Design, PPMS DynaCool). The test temperature is precisely controlled by liquid nitrogen, liquid helium and a heating platform.

[0133] The electrical testing steps include:

[0134] At any temperature in the temperature range of 2 K~300 K, a source-drain voltage is applied in the voltage range of -1 V~1 V with an interval of 5 mV. The current-bias curve of the single-molecule memory is measured as the current changes with the bias voltage, as shown in Figure 3 As shown in the figure, I is the source-drain current and V is the source-drain voltage. Before the molecules are connected, I remains at 0 nA, and after the molecules are connected, I is about 10 nA at a voltage of ±1 V and exhibits nonlinear characteristics, proving that the molecules are successfully connected.

[0135] At any temperature between 2 K and 300 K, apply source-drain voltages of 0.1 V for writing, 0.001 V for reading, -0.1 V for writing, 0.001 V for reading, alternating 100 times without adding gate voltage to test the device read-write stability; Figure 4 The schematic diagram of information reading and writing of the pure electrical single-molecule memory without gate voltage is shown, where the current is 0.1 ~ 10 nA and the time scale is 10 ~ 100 ns. Figure 4 (a) shows that the source-drain voltage is applied in sequence: 1 V for writing, 0.1 V for reading, -1 V for writing, and 0.1 V for reading, and the source-drain current is 10 nA, 0.2 nA, 10 nA, and 0.6 nA, and the reading and writing are continuous for 100 times. Figure 4 Figure (b) shows Figure 4 The curve in the range of 3000 to 4000 ns in Figure (a) is enlarged to show the magnitude of the current more clearly.

[0136] After applying the auxiliary write voltage to the multi-layer stacked wedge-shaped gate of heavy metal, the above writing and reading steps are repeated again to test the speed and power consumption of reading and writing, such as Figure 5 As shown, the schematic diagram of information reading and writing of pure electrical single-molecule memory when gate voltage is applied, where the current is 0.01 ~ 1 nA and the time scale is 1 ~ 10 ns. Figure 5 (a) shows that the source-drain voltage is applied in sequence: 1 V for writing, 0.1 V for reading, -1 V for writing, and 0.1 V for reading, and the source-drain current is 1 nA, 0.02 nA, 1 nA, and 0.06 nA, and the reading and writing are continuous for 100 times. Figure 5 Figure (b) shows Figure 5 The curve in the range of 3000 ~ 4000 ns in Figure (a) is enlarged to show the magnitude of the current more clearly.

[0137] All reactions of the present invention were carried out using standard Schlenk techniques in dry solvents and an inert atmosphere of argon.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A purely electrical single-molecule memory based on spin torque effect, characterized in that: include: Multilayer stacked wedge gates of heavy metals, graphene nanogap array electrodes, organic radical compounds, magnetic tunnel junctions, and nonmagnetic metal electrodes; The organic free radical compound has a chirality-induced spin selection effect to self-assemble into two α-helical structures with opposite chirality, and the organic free radical compound is connected to the graphene nanogap array electrode through an amide covalent bond to form an organic free radical molecular heterojunction; A magnetic tunnel junction and a non-magnetic metal electrode are respectively arranged on both sides of the organic free radical molecule heterojunction, and the graphene nanogap array electrode, the organic free radical compound, the magnetic tunnel junction and the non-magnetic metal electrode are all assembled on the top of the multi-layer stacked wedge-shaped gate of the heavy metal.

2. A pure electrical single-molecule memory based on spin torque effect according to claim 1, characterized in that: The structural formula of the organic free radical compound is: Wherein, n is an integer of 6 to 10; m is an integer of 6 to 10; R is or or or .

3. The pure electrical single-molecule memory based on spin torque effect according to claim 1, characterized in that: The magnetic tunnel junction includes a tunneling layer and a magnetic electrode stacked in sequence, the tunneling layer is connected to the multi-layer stacked wedge-shaped gate of the heavy metal, the tunneling layer includes any one of aluminum oxide, magnesium oxide or molybdenum disulfide, the magnetic electrode includes any one of iron, cobalt or nickel, and the non-magnetic metal electrode includes an adhesive layer and an Au electrode stacked in sequence, the adhesive layer is connected to the multi-layer stacked wedge-shaped gate of the heavy metal.

4. The pure electrical single-molecule memory based on spin torque effect according to claim 1, characterized in that: The heavy metal multilayer stacked wedge-shaped gate comprises a tantalum layer, a cobalt iron boron layer and a tantalum oxide layer stacked in sequence, wherein the bottom is the tantalum layer and the top is the tantalum oxide layer, and the tantalum oxide layer forms a continuously changing thickness gradient along the length direction.

5. The pure electrical single-molecule memory based on spin torque effect according to claim 1, characterized in that: The graphene nanogap array electrode is adapted to the size of the organic free radical compound.

6. The pure electrical single-molecule memory based on spin torque effect according to claim 1, characterized in that: It also includes a hexagonal boron nitride protection layer, which covers the top of the magnetic tunnel junction, the non-magnetic metal electrode and the organic free radical molecule heterojunction.

7. A method for preparing a pure electrical single-molecule memory based on spin torque effect, characterized in that: Preparation of a pure electrical single-molecule memory based on spin torque effect as claimed in any one of claims 1 to 6 comprises the following steps: S1: Preparation of organic free radical compounds; S2: Preparation of heavy metal multilayer stacked wedge-shaped gates; S3: preparing a graphene nanogap array electrode, and preparing an asymmetric magnetic tunnel junction and a non-magnetic metal electrode on both sides of the graphene nanogap array electrode; S4: Connecting organic free radical compounds to graphene nanogap array electrodes through covalent bonds to obtain single-molecule spin memory; S5: Assemble a single-molecule spin memory directly above a multi-layer stacked wedge-shaped gate of a heavy metal and prepare a hexagonal boron nitride protective layer directly above the single-molecule spin memory to obtain a purely electrical single-molecule memory based on the spin torque effect.

8. The method for preparing a pure electrical single-molecule memory based on spin torque effect according to claim 7, characterized in that: S2 includes the following steps: S21: Depositing SiO2 on the thermally oxidized silicon wafer; S22: using DC magnetron sputtering technology to deposit a tantalum layer on SiO2 at room temperature, and a cobalt iron boron layer on the tantalum layer; S23: depositing a tantalum oxide layer on the cobalt iron boron layer, wherein the top tantalum oxide layer grows in a wedge shape to form a continuously changing thickness gradient along the length direction; exposing the layer to radio frequency oxygen / argon plasma to form a tantalum oxide layer, and obtaining a gate sample; S24: annealing the gate sample to obtain a multi-layer stacked wedge-shaped gate of heavy metal.

9. The method for preparing a pure electrical single-molecule memory based on spin torque effect according to claim 7, characterized in that: S3 includes the following steps: S31: growing a single layer of graphene on the surface of copper foil by chemical vapor deposition and transferring it to the surface of silicon wafer by means of polymethyl methacrylate; S32: using an ultraviolet lithography machine to perform a first photolithography, making a marking pattern on the graphene surface and evaporating metal chromium and gold to obtain graphene with a mark; Using an ultraviolet lithography machine to perform a second photolithography, making a stripe pattern on the surface of the labeled graphene, and etching it in a reactive ion etcher to obtain graphene strips; The third photolithography was performed using an ultraviolet lithography machine to make an electrode pattern on the left side of the graphene strip, and magnesium oxide and cobalt were sequentially evaporated by magnetron sputtering to obtain an asymmetric magnetic tunnel junction on the left side of the graphene strip. The fourth photolithography was performed using an ultraviolet photolithography machine to make an electrode pattern on the right side of the graphene strip, and chromium and gold were sequentially evaporated by magnetron sputtering to obtain a non-magnetic metal electrode on the right side of the graphene strip; S33: Spin-coat a polymethyl methacrylate protective layer on the surface of the graphene strip, use electron beam exposure technology to make a polymethyl methacrylate dotted window, use a reactive ion etcher to penetrate the polymethyl methacrylate dotted window to break the graphene into a head-to-head triangular array, and obtain a graphene nanogap array electrode by electrical burning.

10. The method for preparing a pure electrical single-molecule memory based on spin torque effect according to claim 7, characterized in that: S4 includes the following steps: S41: mixing an organic free radical compound and a dehydration activator, and dissolving the mixture in a solvent in an anhydrous and oxygen-free environment to obtain a mixed solution; S42: sealing the device containing the graphene nanogap array electrode in a two-necked flask, repeatedly performing aeration and ventilation operations, adding the mixed solution, making the reaction in an inert gas atmosphere, reacting for 24 to 48 hours under dark conditions, taking out, washing, and drying to obtain a single-molecule spin memory; The dehydration activator is selected from any one of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloric acid, dicyclohexylcarbodiimide or N,N'-diisopropylcarbodiimide; the solvent is selected from any one of pyridine, dimethyl sulfoxide or trichlorobenzene; the inert gas is argon or nitrogen; the molar ratio of the organic free radical compound to the dehydration activator is 1:(20-40); the concentration of the dehydration activator is 2×10 -3 ~ 4×10 -3 mol / L.

Citation Information

Patent Citations

  • Two-bit memory device, and method and electronic component for operating two-bit memory device

    CN114631144A

  • method and calculator for modeling non-equilibrium spin polarized charge transport in nano-structures

    US20080170338A1